One to Two Days of Rest Is Recommended Before Returning to Sport After Intra-Articular Corticosteroid Injection in the High-Level Athlete - Katie McMorrow, B.S; Sachin Allahabadi, M.D; Landon Frazier, B.S; Ryan Quigley, M.D; Brian Serrano, D.C., Ph.D., A.T.C., C.S.C.S; Brian J. Cole, M.D., M.B.A (Elsevier, 2023)
Return to sport following a corticosteroid injection is a complex decision. Multiple considerations should be taken into account, including steroid dose and formulation, involvement of the affected joint in the activity, and intensity of the activity. Research investigating the adverse effects of corticosteroid injections with early initiation of high-intensity activity is limited and has produced mixed results. Rest following injections has typically been recommended to minimize both chondrotoxic effects and systemic absorption. Based on the current research and extensive experience treating professional athletes, we recommend 1 to 2 days of rest of the affected joint or region with a progressive increase of activity following a corticosteroid injection with possible benefits including maximizing the beneficial effects of the injection and a reduced systemic effect. Level of Evidence: Level V, expert opinion.